Docentes no exercício da gestão em uma IFES: desafios e perspectivas - Nunes, Lindojane Gomes (2020)
This paper examines the complex experience of the management of teaching staff in a Federal Institution of Higher Education (IFES), in particular the professors within their functions of university administration, academic management at the Humanities Center of the Federal University of Ceará-UFC. The research gathered its main sources from the Professional Training Division (DIFOP), the Academic School for Development and Academic Innovation (EIDEIA), the Professional Master in Public Policy and Higher Education Management (POLEDUC), as well as from the literature produced in the university management area of the IFES´s. The work is also contextualized in a current history perspective of higher public education. Set in clashes and / or controversies generated by the application of contingency measures and cuts in the public budget for higher education, as well as the deadlocks generated around the “Future-se” program. Concerning the main subject of the Dissertation, our attention turned to the application of a questionnaire to teachers in a managerial role in different sectors such as Coordination of Undergraduate and / or Postgraduate Courses, Head of Departments and Houses of the Culture Humanities Center (CH / UFC); as a mechanism of qualitative analysis. This research, based on the analysis of conceptual and empirical data, highlights the specific meanings of teaching in an IFES, observing its difficulties and challenges, as well as points out perspectives regarding the improvement of management. Supported by the analysis of the collected data, the study wishes to contribute towards the granting of subsidies so that, within the UFC, the debates and effective instruments for the consolidation of a permanent training policy aimed at the university management, regarding the equipping of the necessary resources to be extended. Achievement of good practices in the exercise of university management.